Development of smart industry as an efficient way to implement the policy of neoindustrialization in the world - Kniaziev, S.I. (Економіка промисловості, 2017)
The paper reveals modern trends of development of manufacturing systems, based on the principles of the Forth Industrial Revolution and linked with transition to the smart industry principles.Smart enterprise is considered as the key primal segment of smart industry construction, which characterized with the possibility of control and tracking of industrial tools and industrial staff functioning through the Industrial Internet of Things. It also allows using data, collected for increasing productivity of labour, modification of technological processes and production quality. Nowadays a number of countries all around the world formatted their own strategies of national mechanisms of smart industry’s incipience. At the same time, there are some similarities and differences in the formatting of principles and implementation of approaches that can be observed in this context in leading industrial countries. German’s concept “Industry 4.0” was formed with the direct participation of governmental structures, scientific and business circles and considered the development of national industry, but not the global breakthrough. Implementation of this concept is directed on supporting of small and medium national manufacturers. In the USA the Industrial Internet Consortium was created as a non-commercial organization with open membership. Promoting the concepts of “sharing” and “open platforms”, Consortium considers its main task to be an optimization of profitable assets with emphasize on total financial returns. Chinese “Made in China 2025” strategy was formed upon the initiative of the government and assumed its leading role in the management of economy and transformation processes. The strategy defines an ambitious task as the main goal - to turn China into the world leading manufacturer and high-tech state through the increasing of “intellectual” smart industry capacity by 2025.Different appraisals of the abovementioned countries’ prospects of the programs implementation show that today progressive businessmen no longer believe that transfer of production capacities to countries with cheap labour is a reliable way to succeed. This is due to the fact that goods have to fit the configuration of manufacturing, directed on satisfying the individual consumers’ needs and requests. From now on, the industry can become more localized. On the other hand, development of a smart industry means qualitative leap in cooperation and coordination of enterprises, linked through the global computer networks with researchers, developers, suppliers, distributors, end-users, etc. all around the world. Ukraine must form its own program of national manufacturing transition to “smart” grounds, because the analysis of foreign experience, conducted in the paper, reveals an in expediency of “blindly copying” the foreign strategies. Given the current state of affairs, combined model of building the smart industry can be congruent one for Ukraine. This model represents a combination of profitable assets optimization (according to the US experience) and support of national small and medium businesses (according to the German experience). The latter can provide fast integration into world smart environment, development and export of the necessary advanced technologies and products for the network industry under existing circumstances. Розкрито особливості промислового смарт-підприємства (як гнучкого кіберфізичного виробництва, що забезпечує точне налаштування на споживача і ґрунтується на використанні великих даних), а також старт-промисловості. Проаналізовано етапи реіндустріалізації провідних країн на шляху до розбудови смарт-промисловості. Визначено нові перспективи, можливості та проблеми, пов’язані з розвитком смарт-промисловості. Раскрыты особенности промышленного смарт-предприятия (как гибкого киберфизического производства, которое обеспечивает точную настройку на потребителя и базируется на использовании больших данных), а также смарт-промышленности. Проанализированы этапы реиндустриализации ведущих стран мира на пути к построению смарт-промышленности. Определены новые перспективы, возможности и проблемы, связанные с развитием смарт-промышленности.